PELATIHAN PEMASARAN PRODUK KERIPIK CABE MELALUI MEDIA SOSIAL BAGI WARGA ASRAMA BRIMOB BATALYON B MALANG - Ellyn Eka Wahyu; Yekie Senja Oktora; Halid Hasan; Siti Nurbaya; Eny Widiyowati (P3M Politeknik Negeri Malang, 2022)
This Community Service (PPM) activity is carried out as a responsibility in fulfilling the obligations of the Tri Dharma of Higher Education. The target objects in this PPM activity are women from the Asrama Brimob Batalyon B Pelopor, Kelurahan Ampeldento, Kecamatan Pakis, Kabupaten Malang. This PPM activity seeks to provide understanding through materials and guidance to promote the sale of chili chips using social media. This guidance is given to the public through material presentation activities and hands-on practical activities on how to create written and photo content which will later be used as material to promote chili chips products so that they are expected to get customers outside the Asrama Brimob Ampeldento. From this Community Service (PPM) activity, it is hoped that a synergy will be created between the women of the Asrama Brimob Batalyon B Pelopor Kabupaten Malang and the Malang State Polytechnic, that this guidance activity can help partners in increasing their income through promotional activities and sales of chili chips by use social media continuously.